Market entry strategy for E.daniely - Štěpánek, Martin; Tyll, Ladislav; Srivastava, Mohit; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
The thesis aims to provide a recommendation to the Czech fashion producer E.daniely to which new international market it should expand with its products and what mode of entry it should select. In the theoretical part, the literature written on topics such as internationalization, market selection process and entry modes is reviewed and the reader is familiarized with widely used strategy frameworks that are later used in the practical part of the thesis. The first half of the practical part introduces the company and outlines the methodology of how the most promising country will be selected. In the second half, the data collected by the desk research are presented and the countries are quantitatively assessed. It was concluded that E.daniely should start its international expansion by exporting to Austria through a company’s sales representative.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses